Management model of industry-integrated education financing (MPTI) to improve education quality in vocational schools - Priyanta, Priyanta; Sudarsono, Bambang (Jurnal Taman Vokasi, 2024)
In 2023, vocational high schools (VHS) accounted for the largest amount of unemployment above 9.2%. Unemployment occurs because the quality of education is still low. Improving the quality of vocational education that is integrated with industry is very important in supporting national economic development and reducing unemployment. By integrating industry needs in the education financing model, it is expected to create a learning environment/climate that is in accordance with industry standards and needs. The purpose of this research is to design an education financing management model that is integrated with industry needs. The design of a well-implemented industry-integrated SMK financing model is expected to improve the quality of education so as to reduce the unemployment rate of SMK graduates. The research design used adopted the research and development (R&D) design of Richey and Klein by taking 3 stages, namely needs analysis, model design and validation. The research was conducted at SMK N 1 Trucuk Klaten and SMK Muhammadiyah Pakem with the research subjects being the principal, treasurer, automotive engineering vocational teachers and industry practitioners. Data collection techniques used non-test data with interview instruments through FGD activities and validation/feasibility questionnaires for experts. Data analysis used quantitative analysis and formulated the results with categorization. The results concluded that the industry-based education financing model (MPTI) has very good feasibility with an average score of 3.71 on a scale of 4. This model is considered very appropriate to the needs, effective, able to collaborate with industry, sustainable, provides significant benefits, and is easy to use.